Partus alendus est - Bellodi Ansaloni, Anna (Tesserae iuris, 2023)
The essay illustrates characteristics and implications of the praetorial provision of missio in possessionem ventris nomine under the perspective of the alimenta regarded as essential for the growth of the embryo. The peculiar situation of the pregnancy is the core of the regulation in which many interests meet: the father’s desire for issue, the profits that the res publica would gain from a future citizen, the protection and the hereditary expectations of the venter and, eventually, the indirect and temporary interest of the mother to receive the alimenta throughout the whole pregnancy.